Unirismo and Pluma Libre. Expressions and Transformations of Gaitanist Newspapers of 1930’s - Charry Joya, Carlos Andrés (Sociedad y Economía, 2019)
The main objective of this article is to analyze the contents and transformations of the gaitanist newspapersUnirismo y Pluma Libre. To achieve this goal, the methodology developed is based on an approach to thediscursive strategies through which the members of the gaitanist movement shaped a set of opinions andpolitical actions. The interpretation that is made, begins at the conceptualization of such media ascognitive entrepreneurs. As a general conclusion of the analysis proposed, the organizational and ideological difficulties experienced by the Gaitanist movement in its initial stages are recognized, as well the intricate relationships it had with the Liberal Party and with the rest of the left wing organizations of the period.